ANALISIS PERPUTARAN MODAL KERJA DAN RENTABILITAS PADA KOPERASI SIMPAN PINJAM MANDIRI BINA LESTARI PINANGSORI KABUPATEN TAPANULI TENGAH - PEBRIANI KRISTINARTI HALAWA; FAUZIAH NUR SIMAMORA; Safriadi Pohan (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
ABSTRACT This study aims to describe the turnover of working capital of the Bina Lestari Pinangsori Mandiri Savings and Loans Cooperative in Central Tapanuli Regency and to explain the level of profitability of the Bina Lestari Pinangsori Mandiri Savings and Loans Cooperative in Central Tapanuli Regency. The research method used is descriptive method with analysis of working capital turnover ratios (cash turnover ratios, accounts receivable turnover, inventory turnover), and profitability ratios (total asset turnover). The results of the analysis show that the working capital turnover of the Mandiri Bina Lestari Pinangsori Savings and Loans Cooperative, Central Tapanuli Regency for 2019-2021 based on the cash turnover ratio and inventory turnover ratio is considered good or effective, and based on the accounts receivable turnover ratio it is very slow so it is considered ineffective. Meanwhile, based on the ratio of asset profitability achieved, it shows that the Bina Lestari Pinangsori Mandiri Savings and Loans Cooperative in Central Tapanuli Regency is not yet profitable. Keywords: Working capital, Profitability